Economic preferences and state-level corruption: global evidence and mechanism. Issue 7 (16th April 2023) - Yang, Xiaolan; Huang, Yidong; Li, Wenchao
ABSTRACT: Using newly published data from the Global Preference Survey which cover 76 countries (Falk et al., 2018), we document robust evidence that economic preferences are partly responsible for state-level corruption. Specifically, fixed effects estimation results show that patience, trust, and altruism discourage corruption, while negative reciprocity encourages corruption. We examine the role of economic freedom and government effectiveness as the mechanisms underlying the effect of negative reciprocity. We also find that the effects of patience and negative reciprocity are greater in a more stable political environment, and smaller in a society with faster economic growth.